Climate change and extreme events: Impacts on Pakistan’s agriculture - Zhu, Tingju; Xie, Hua; Waqas, Ahmad; Ringler, Claudia; Iqbal, M. Mohsin; Goheer, M. Arif; Sulser, Timothy B. (International Food Policy Research Institute, 2014)
Due to its arid to semi-arid climate, water is the single most constraining factor to Pakistani agriculture. Water resources are heavily appropriated for productive uses, and agriculture is the main user of water resources. Over eighty percent of crop value comes from irrigated agriculture. Demand for water is increasing from population growth and industrial and agricultural development. Moreover, water resources are threatened by drought and long-term climate change through its effect on temperature, precipitation, and glacier runoff.